Robot Intelligence Technology and Applications 2 Results from the 2nd International Conference on Robot Intelligence Technology and Applications - Kim, Jong-Hwan.; Matson, Eric T .; Myung, Hyun.; Xu, Peter; Karray, Fakhri; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
We are facing a new technological challenge on how to store and retrieve knowledge and manipulate intelligence for autonomous services by intelligent systems which should be capable of carrying out real world tasks autonomously. To address this issue, robot researchers have been developing intelligence technology (InT) for “robots that think” which is in the focus of this book. The book covers all aspects of intelligence from perception at sensor level and reasoning at cognitive level to behavior planning at execution level for each low level segment of the machine. It also presents the technologies for cognitive reasoning, social interaction with humans, behavior generation, ability to cooperate with other robots, ambience awareness, and an artificial genome that can be passed on to other robots. These technologies are to materialize cognitive intelligence, social intelligence, behavioral intelligence, collective intelligence, ambient intelligence and genetic intelligence. The book aims at serving researchers and practitioners with a timely dissemination of the recent progress on robot intelligence technology and its applications, based on a collection of papers presented at the at the 2nd International Conference on Robot Intelligence Technology and Applications (RiTA), held in Denver, USA, December 18-20, 2013.
Ambient, Collective, Cognitive and Social Intelligence -- Behavioral, Collective and Genetic Intelligence -- Emerging Applications of Robot Intelligence Technology.
Keywords: Computational intelligence; Artificial intelligence; Robotics; Automation; Computational Intelligence; Artificial Intelligence; Robotics and Automation